Delamination Localization in Multilayered CFRP Panel Based on Reconstruction of Guided Wave Modes - Mastan Raja Papanaboina; Elena Jasiuniene; Vykintas Samaitis; Liudas Mažeika; Paulius Griškevičius (Applied Sciences, 2023)
Multi-layered composite materials are being used in various engineering fields, such as aerospace, automobile, and wind energy, because of their superior material properties. Due to various impact loads during the service life of composite structures, different types of defects can occur, such as matrix cracking, fiber breakage, delaminations, etc. In this research, a novel SHM technique for delamination detection and localization using a minimum number of sensors is proposed. The analytical, numerical, and experimental analysis of GW was performed to increase the probability of detection and localization of delaminations in CFRP material. A new analytical model was developed, which enables identifying converted and transmitted modes in the presence of multiple GW modes. A 2D FFT-based spatial filtering was used to filter the GW modes. The dominant A0 mode was separated to inspect the delamination. Phase velocity is one of the important features in GW inspection to localize the delamination. A phase spectrum approach was developed to reconstruct the phase velocity dispersion of the GW modes in case material properties are unknown.